Seven-Year Surveillance of the Clinical Performance of a Blood Glucose Test Strip Product. (November 2017) - Setford, Steven; Grady, Mike; Phillips, Stuart; Miller, Lesley; Mackintosh, Stephen; Cameron, Hilary; Corrigall, Krisna
Background: A key approach in enabling people with diabetes to better manage their condition is through self-monitoring of blood glucose (SMBG). Any functional SMBG system should demonstrate clinical accuracy across a broad glucose range and be insensitive to hematocrit. Furthermore, it should be incumbent on the manufacturer to demonstrate that their product continues to meet clinical accuracy claims during product lifetime. Methods: Test strips from a globally distributed SMBG product were sampled from randomly selected production batches as part of the manufacturer's routine product evaluation process. Clinical accuracy was assessed within diabetes patients at 3 clinic sites against a standard reference method and evaluated against system accuracy in accordance with the ISO 15197:2015 standard (unchanged from ISO 15197:2013 in terms of performance specifications). Data were collected over 7 years (2010-2016) and comprised 73, 600 individual glucose results. Overall clinic performance was assessed, as was accuracy at low and high glucose levels and extremes of hematocrit. Results: Across the 7-year surveillance period, overall test strip clinical accuracy was 97.8% versus the 95% ISO-defined minimum criterion with by-year values of 97.0-98.6%. Accuracy at the lowest (≤50 mg/dL) and highest (>400 mg/dL) ranges of glucose was 97.0% and 98.3% respectively. Within these low/high blood glucose subpopulations, accuracy at the lower and upper first percentile hematocrit ranges, was 98.9%, and 97.1% respectively. Conclusions: This 7-year surveillance program showed the test strips to have excellent clinical accuracy at the outer ranges of subject blood glucose and hematocrit, based on assessment against the ISO 15197:2015 clinical accuracy criterion.